Orange peel valorization by pyrolysis under the carbon dioxide environment. (August 2019) - Kwon, Dohee; Oh, Jeong-Ik; Lam, Su Shiung; Moon, Deok Hyun; Kwon, Eilhann E.
Graphical abstract: Highlights: Valorization of orange peel via the pyrolysis process was conducted. To establish a more sustainable pyrolytic platform for orange peel, CO2 was used. CO2 suppressed dehydrogenation of volatile matters (VMs) derived from orange peel. The reactions of VMs and CO2 resulted in the enhance generation of CO2 at ≥550 °C. Abstract: To valorize biomass waste, pyrolysis of orange peel was mainly investigated as a case study. In an effort to establish a more sustainable thermolytic platform for orange peel, this study particularly employed CO2 as reactive gas medium. Accordingly, this study laid great emphasis on elucidating the mechanistic role of CO2 in pyrolysis of orange peel. The thermo-gravimetric analysis (TGA) confirmed that no occurrence of the heterogeneous reactions between the solid sample and CO2 . However, the gaseous effluents from pyrolysis of orange peel experimentally proved that CO2 effectively suppressed dehydrogenation of volatile matters (VMs) evolved from the thermolysis of orange peel by random bond scissions. Moreover, CO2 reacted VMs, thereby resulting in the formation of CO. Note that the formation of CO was being initiated at temperatures ≥550 °C. The two identified roles of CO2 led to the compositional modification of pyrolytic oil by means of lowering aromaticity.